Sustainable Dry Land Management Model on Corn Agribusiness System - Pujiharti, Yulia; Haridjaja, Oteng; Eriyatno, .; Rusastra, I Wayan (JOURNAL OF TROPICAL SOILS, 2008)
The study aimed at building model of dry land management.  Dynamic System Analysis was used to build model and Powersim 2.51 version for simulating.  The parameter used in model were fertilizer (urea, SP-36, ACL), productivity (corn, cassava, mungbean), soil nutrient (N, P, K), crop nutrient requirements (corn, cassava, mungbean, mucuna), price (corn, cassava, mungbeans corn flour, feed, urea, SP-36, KCl), food security credit, area planted of (maize, cassava, mungbean), area harvested of (maize, cassava, mungbean), (corn, cassava, mungbean) production, wages and farmer income.  Sustainable indicator for ecology aspect was soil fertility level, economic aspects were productivity and farmer income, and social aspects were job possibility and traditions.  The simulation result indicated that sustainable dry land management can improve soil fertility and increase farmer revenue, became sustainable farming system and farmer society. On the other hand, conventional dry land management decreased soil fertility and yield, caused farmer earnings to decrease and a farm activity could not be continued.  Fertilizer distribution did not fulfill farmer requirement, which caused fertilizer scarcity.  Food security credit increased fertilizer application.  Corn was processed to corn flour or feed to give value added.